Evaluation of a positive psychotherapy group intervention for people with psychosis: pilot randomised controlled trial - Schrank, Beate; Brownell, Tamsin; Jakaite, Zivile; Larkin, Charley; Pesola, Francesca; Riches, Simon; Tylee, Andre; Slade, Mike (Cambridge University Press, 2016)
Aims. Third-wave psychological interventions have gained relevance in mental health service provision but their application to people with psychosis is in its infancy and interventions targeting wellbeing in psychosis are scarce. This study tested the feasibility and preliminary effectiveness of positive psychotherapy adapted for people with psychosis (WELLFOCUS PPT) to improve wellbeing. Methods. WELLFOCUS PPT was tested as an 11-week group intervention in a convenience sample of people with psychosis in a single centre randomised controlled trial (ISRCTN04199273) involving 94 people with psychosis. Patients were individually randomised in blocks to receive either WELLFOCUS PPT in addition to treatment as usual (TAU), or TAU only. Assessments took place before randomisation and after the therapy. The primary outcome was wellbeing (Warwick-Edinburgh Mental Well-Being Scale, WEMWBS). Secondary outcomes included symptoms (Brief Psychiatric Rating Scale), depression (Short Depression-Happiness Scale), self-esteem, empowerment, hope, sense of coherence, savouring beliefs and functioning, as well as two alternative measures of wellbeing (the Positive Psychotherapy Inventory and Quality of Life). Intention-to-treat analysis was performed. This involved calculating crude changes and paired-sample t-tests for all variables, as well as ANCOVA and Complier Average Causal Effect (CACE) Analysis to estimate the main effect of group on all outcomes. Results. The intervention and trial procedures proved feasible and well accepted. Crude changes between baseline and follow-up showed a significant improvement in the intervention group for wellbeing according to all three concepts assessed (i.e., WEMWBS, Positive Psychotherapy Inventory and Quality of Life), as well as for symptoms, depression, hope, self-esteem and sense of coherence. No significant changes were observed in the control group. ANCOVA showed no main effect on wellbeing according to the primary outcome scale (WEMWBS) but significant effects on symptoms (p = 0.006, ES = 0.42), depression (p = 0.03, ES = 0.38) and wellbeing according to the Positive Psychotherapy Inventory (p = 0.02, ES = 0.30). Secondary analysis adapting for therapy group further improved the results for symptom reduction (p = 0.004, ES = 0.43) and depression (p = 0.03, ES = 0.41) but did not lead to any more outcomes falling below the p = 0.05 significance level. CACE analysis showed a non-significant positive association between the intervention and WEMWBS scores at follow-up (b = 0.21, z = 0.9, p = 0.4). Conclusions. This study provides initial evidence on the feasibility of WELLFOCUS PPT in people with psychosis, positively affecting symptoms and depression. However, more work is needed to optimise its effectiveness. Future research might evaluate positive psychotherapy as a treatment for comorbid depression in psychosis, and consider alternative measurements of wellbeing.